Screening of antioxidant, antimicrobial and antiradical activities of twelve selected Serbian wild mushrooms. Issue 10 (21st May 2015) - Dimitrijevic, Marija; Jovanovic, Vesna Stankov; Cvetkovic, Jelena; Mihajilov-Krstev, Tatjana; Stojanovic, Gordana; Mitic, Violeta
<x xml:space="preserve">Abstract</x> The CUPRAC method was applied for the first time to estimate the antioxidant activity of some mushrooms.